Centro de procesos de reciclaje de las 3R para mejorar las condiciones productivas de los recicladores en la localidad de Kennedy, Bogotá. (2022)
The area used in the developed project is located in Colombia, in the city of Bogotá, specifically in the town of Kennedy. The first stage of intervention is carried out at these three points, analyzing the territory, its location and its main characteristics. At the Colombian level, a main problem was established: the uncontrolled generation of waste and the lack of viable and functional collection systems, which has repercussions in Bogotá and in turn in one of the largest towns in the city. The line of investigation according to the data collected and presented directed the project to be located in this locality due to the amount of waste that is discarded daily. A comprehensive network is proposed that, taking into account the current cultural and social conditions of recyclers, achieves their link to formality and improves their working conditions, all revolving around the modernization and improvement of recycling processes.